Analisis urgensi kompetensi kepribadian guru - Nilma Zola; Mudjiran Mudjiran (Indonesian Institute for Counseling, Education and Therapy (IICET), 2020)
Qualified teachers must be professional, have new strength and responsibility to plan for future education, and have skills and meet the professional competence of teachers. Competence is a set of knowledge, skills, and behaviors that the teacher must have, live, and master. Personality competence is one of the four professional competencies that a teacher must possess. Teachers are not only required to explain learning material to students, but teachers also have the responsibility to increase the potential and also the quality of students’ personalities, so that in order to do this, of course, the teacher must also have good personality competencies.